2015
DOI: 10.1080/02640414.2015.1117121
|View full text |Cite
|
Sign up to set email alerts
|

Technical performance and match-to-match variation in elite football teams

Abstract: Recent research suggests that match-to-match variation adds important information to performance descriptors in team sports, as it helps measure how players fine-tune their tactical behaviours and technical actions to the extreme dynamical environments. The current study aims to identify the differences in technical performance of players from strong and weak teams and to explore match-to-match variation of players' technical match performance. Performance data of all the 380 matches of season 2012-2013 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
189
5
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(220 citation statements)
references
References 39 publications
19
189
5
7
Order By: Relevance
“…"weak" or "strong" and their position on league rankings), and match status (if winning, losing or drawing) were identified as the most important situational variables that dictates possession patterns [9][10][11][12][13] . Concerning match location, playing home presented stronger interaction with team possession than playing away 6,8,14 , which might be explained by a more familiar environment and a more consistent style of play 15,16 . The quality of opposition is also a determinant variable when investigating possession in soccer 12,16 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…"weak" or "strong" and their position on league rankings), and match status (if winning, losing or drawing) were identified as the most important situational variables that dictates possession patterns [9][10][11][12][13] . Concerning match location, playing home presented stronger interaction with team possession than playing away 6,8,14 , which might be explained by a more familiar environment and a more consistent style of play 15,16 . The quality of opposition is also a determinant variable when investigating possession in soccer 12,16 .…”
Section: Introductionmentioning
confidence: 94%
“…Concerning match location, playing home presented stronger interaction with team possession than playing away 6,8,14 , which might be explained by a more familiar environment and a more consistent style of play 15,16 . The quality of opposition is also a determinant variable when investigating possession in soccer 12,16 . According to Taylor,Mellalieu 10 , when facing strong opponents, teams perform more passes and fewer dribbles.…”
Section: Introductionmentioning
confidence: 94%
“…Due to the availability of data, the profiling subject has developed over time from the analysis of single players or teams to more comprehensive analysis including a larger number of players or teams [15]. Previously, median and 95% confidence intervals [9,16] were used to present the typical performance of subjects and its spread of performance, while currently profiling techniques are commonly based on mean and 95% confidence intervals [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature of complexity and highly dynamic behaviour in football matches [18][19][20][21], the match performance of players/teams is not only influenced by technical, tactical, mental [22,23], and physiological factors [24], but also by different situational factors [25,26]. Match performance of players/teams cannot be generalized in all contexts [15] and introducing the situational variables into performance profile can make it more comprehensive and systematic [17]. Match location, team quality, quality of opposition, and match outcome are examples of situational variables that have been investigated so far [17,18,27].…”
Section: Introductionmentioning
confidence: 99%
“…This trend was consistently born out across all of the playing surfaces, small-sided game formats and age groups observed in this study. As such, it can be confirmed that those attacking moves were essential to finishing off attacking moves successfully (Liu et al, 2015a). In the same way, entries into the area box also significant in the majority of attacks analysed (reaching up to 13.5 entries into the box per match in the 5v5 format), including passes, dribbles and shots as essential variables in those entries (Folgado et al, 2015).…”
Section: Passing Dribbling and Shooting Are The Most Used Attacking mentioning
confidence: 60%